Consumption of polysaccharides from Auricularia auricular modulates the intestinal microbiota in mice. (September 2019) - Zhao, Ruiqiu; Cheng, Ninghui; Nakata, Paul A.; Zhao, Liyan; Hu, Qiuhui
Abstract: The objective was to determine the contribution of A. auricular polysaccharides (AAP) in modulating the composition and diversity of the intestinal microbe in mice. AAP was extracted from A. auricula freeze-dried powder and different amounts of AAP (40, 80, 160 mg AAP/kg body weight) were administered to 6 week-old male ICR mice by gavage feeding over a five-week period. AAP feeding changed the intestinal environment in the mice. The pH value of the intestinal compartments decreased while SCFAs concentrations increased in AAP-fed groups, in a dose dependent manner, compared to the controls ( P < .05). High throughput sequencing revealed an enrichment in the diversity and an alteration in the composition of the fecal microbiota in the AAP fed mice with a significant decrease in the Firmicutes/Bacteroidetes ratio ( P < .05). The relative abundances of Porphyromonadaceae and Bacteroidaceae also increased in the AAP fed mice which positively correlated with an increase in serum IgA and IgG concentrations ( P < .05). The findings from this study show that AAP modulates the mouse gut microbiota and may contribute, at least in part, to some of the reported beneficial effects from the consumption of the mushroom, A. auricula . Graphical abstract: Unlabelled Image Highlights: The polysaccharide from Auricularia auricular were extracted and analyzed its character. By animal experiment, AAP can reduce the pH value and increase the content of SCFAs in mice intestinal lumen. AAP has the capacity to increase microbial community diversity and alter the composition of fecal microbe. AAP can increase the immunoglobulin in mice serum.